Human brucellosis exposure in confirmed cutaneous anthrax cases, Dien Bien, Vietnam with an update on human prevalence regionally - Blackburn, J.; Pham Quang Thai; Luong Mihn Tan; Zincke, D.; Nguyen Van Long; Nguyen Khanh Ly; Long Thanh Pham; Hung Nguyen-Viet; Hu Suk Lee; Tran Thi Mai Hung; Hadfield, T.L.; Hoang Thi Thu Ha (2022)
Anthrax and brucellosis are important zoonoses worldwide. Often, they are reported separately with separate control strategies in livestock; routine vaccination for both accompanied by culling for brucellosis. The status of both diseases is poorly understood in Vietnam. In Vietnam, anthrax has been identified as a priority zoonotic disease for control in a One Health Circular (#16, 2013). Vietnam has a likely substantial, but poorly understood, brucellosis risk. There were no data available for Vietnam in the 2006 global assessment. Brucellosis rates are unknown, but the disease has been confirmed for humans and livestock, including recent genotyping in southern provinces. Here, we implemented the fluorescence polarization assay (FPA) using the Sentry 200 handheld FPA reader (Ellie Labs) and the B1002 test kits (based on an O-polysaccharide for Brucella abortus, which also reacts with B. suis and B. melitensis). We performed tests on human and animal samples. Human serum samples (collected 2011-2016) were randomly selected from the NIHE serum bank and livestock samples were provided from NCVD and NIHE (2015 - 2018); additional swine samples were provided by ILRI. We are currently running active hospital surveillance across six provinces in northern Vietnam, with 1,018 samples collected to date and 312 tested. We confirmed 1.39% human exposure to brucellosis (5/359; 95% CI: 0.045% - 3.22%). Four of those exposures were detected in Dien Bien province and two of those were confirmed cutaneous anthrax cases. The two co-infections were detected in family members from a single household in 2011 with the remaining two cases independent of each other in 2015. The fifth case was reported from Ha Nam province in 2016. These results suggest brucellosis may be widespread underappreciated/underreported in Vietnam. Preliminary results from ongoing surveillance suggest similar prevalence rates. We tested 1107 animals. While human samples were limited to northern Vietnam, animal samples were widely distributed. Domestic swine from southern Vietnam were 9.4% (17/180) seropositive. A second group of swine samples from ILRI had 2.2% seroprevalence (11/500). The remaining samples represented domestic cattle/buffaloes; all sero-negative. Our results suggest brucellosis surveillance for Vietnam is warranted and future policy might list brucellosis as reportable.